A cobalt and nickel co-modified layered P2-Na2/3Mn1/2Fe1/2O2 with excellent cycle stability for high-energy density sodium-ion batteries - Chu, S.; Chen, Y.; Wang, J.; Dai, J.; Liao, K.; Zhou, W.; Shao, Zongping (Elsevier B.V., 2019)
© 2018 Considering the abundant sodium resources, sodium-ion batteries (SIBs) demonstrate great potential in large-scale electrochemical energy storage sectors which capacity and cycle stability is highly dependent on their electrode materials. Layered P2-type Mn-Fe-based oxide has been considered as one of the most promising cathodes for SIBs, while its unsatisfactory cycle performance and low energy density strongly limit practical application. Here, a Co/Ni modification strategy is proposed to optimize P2-Na2/3Mn1/2Fe1/2O2 (MF) from both aspects of reversible capacity and cycle stability, leading to the design of a new P2-Na2/3Mn1/2Fe1/4Co1/8Ni1/8O2 (MFCN). In this new layered P2-type material, the introduction of Co effectively inhibits the irreversibility of the material, and the introduction of Ni relieves the Jahn-Teller effect and reduces Mn dissolution. The simultaneous introduction of Co and Ni effectively improves the cycle stability of the electrode, indicated by the increase of the capacity retention rate from 51.5% for MF to 87.4% for MFCN over 100 discharge-charge cycles at the same current density of 130 mA g-1. Meanwhile, the introduction of Ni effectively increases the discharge voltage with the middle discharge voltage increasing from 2.8 V (MF) to 3.3 V (MFCN), thereby improving the energy density of the electrode. All above features make the new material highly promising for use as a cathode material in practical SIBs.